Time-Frequency and Fractal Analyses of the Earth's Magnetic Field Variations Appeared During Powerful Geospace Storms Took Place in September 2017 - Chernogor, L.; Lazorenko, O.; Onishchenko, A. (Taras Shevchenko National University of Kyiv Astronomical Observatory, 2021)
According to the non-linear and the system paradigms, many processes generated in open, non-linear, dynamical systems under influence of a powerful source of energy release are appeared to be short-time, ultrawideband, non-linear and fractal.